Word-Building Potential of the Word “Ақ” in the Modern Kazakh Language - Shokabayeva С.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
In the Kazakh language, the word «aқ» belongs to words that have a lot of meanings. In our language, this word is the basis for many derived words used as nouns, adjectives and qualitative meanings. In the article, the word-building potential of the word «ақ» in the modern Kazakh language is determined using the analysis of the derirational faruly. The linguistic data and derived words are collected from the dictionaries of the scientist B. Kasim «Kördelі Zat Esіmder Sөzdіgі» («Complex Nouns Dictionary») and «Kazak Adebi Tіlіnіn Sozdіgі» («Dictionary of the Kazakh Literary Language»). The article discusses the works of scientists who have studied the, as well as revealed 211 derivatives formed from the word «aқ». In addition, it is proved that 15 derived words are formed by synthetic, 21 by lexicosemantic, 175 by analytical methods of word-formation, 202 word-formation pairs, 174 word-formation chains, 3 word-formation paradigms and 6 word-formation ladders.